Prevalence and Bacteriological Profile of Healthcare-Associated Pathogens Isolated from Basra Hospitals - Abdulridha, Lamyaa; Abdulsayed, Shafeeqa (Journal of Contemporary Medical Sciences, 2025)
Objective: Nosocomial infections- especially bacterial infections- are a major concern in healthcare, creating significant risks to both patients and healthcare staff. Given the prevalence of nosocomial infections, the lack of this type of study in Basra province, southern Iraq, is a significant oversight that must be addressed. For the above reason, this study amid to provide appropriate diagnosis for pathogenic bacteria isolated from intensive care unit (ICUs) and operating room (OR) environments at three major hospitals in Basra southern Iraq and to identify the source of bacterial contamination inside these hospitals. Methods: two hundred and ten swab samples were collected from ICU and OR environments including inanimate objects, medical devise, health care attire. Bacteria were isolated using standard microbiology techniques. VITEK® 2 system and 16S rDNA sequencing were used for bacterial identification. Results: showed 69 (32.857%) samples were positive for bacterial growth. 39 (56.521%) isolates classified as Gram-positive, and 30 (43.478%) isolates classified as Gram-negative. According to the VITEK®2 system and 16S rDNA sequencing, the most prevalent species among Gram positive bacteria was Staphylococcus aureus with 10 (14.493%) isolates. While the most prevalent species among Gram negative was Klebsiella pneumoniae with 8 (11.594%) isolates. Conclusions: The study revealed a moderate degree of bacterial contamination on surfaces and equipment within ICUs and ORs of the investigated hospitals.